“Las rondas Infantiles en el desarrollo de la psicomotricidad gruesa de los niños de Educación Inicial” - Paredes Molina, Aracelly Mireya (2024)
Children's rounds are of great importance in Initial Education, since effectively favor the children comprehensive development from 3 to 4 years old, the objective set was to diagnose gross psychomotor skills at the children of the 14 de Julio Juan Abel Echeverria Elementary School. On the other hand, the purpose was to determine how recreational activities and children's rounds benefit the gross psychomotor skills development and children dynamic balance. It is recommended to develop motor activities to stimulate psychomotor development, for which a qualitative approach methodology, related to non-experimental design. The research was developed with inductive, bibliographic and field methods. The observation technique was applied; As an instrument, the checklist was applied, which served to collect information from the children, in this way the difficulties that affect the teaching and motor learning processes were evident. To counteract these results, a children's rounds guide was developed which is made up of 15 activities, therefore, each of them consists of a plan and a checklist, focused on the gross psychomotor area. These rounds are useful, for that teachers implement recreational and playful strategies and maximize gross psychomotor skills and abilities in infants.